Earthquake - Science in Himalayas: Ground Water Quality Change and its Implications - Banjara, Sushant; Paudel, Shukra Raj (Journal of the Institute of Engineering, 2018)
In this paper, we discuss the pre-earthquake and post-earthquake groundwater scenario in context of Nepal. Nepal being one of the most earthquake vulnerable countries, the implications of earthquake in Nepal is considerable. Study requires not so only above the earth surface, but also in sub-surface conditions. Of various geo-physical and geo-chemical, subsurface conditions, this particular study concerns with groundwater chemical parameters. Before the occurrence of earthquake, groundwater chemistry has been found to change in numerous instances as promising precursor of earthquake. On the other hand, the chemical changes in groundwater have been found to continue beyond the occurrence of earthquake. Some of these changes, due to their toxic nature, are likely to cause health hazards to people who directly consume groundwater. In this premise, we deduce that constant observation of groundwater chemistry before and after earthquake is crucial for both earthquake prediction science and for monitoring health risks that may arise from consuming chemically altered groundwater due to tectonic activity. Journal of the Institute of Engineering, 2017, 13(1): 201-205